Pelatihan Konten Manajemen Komunikasi Digital pada Entitas Wisata Mangrove Kedatim Kabupaten Sumenep berbasis Blue Economy - Kurniawan, Rio; Fajar, Fajar; Kurli, Anis (Jurnal SOLMA, 2025)
Background: The Mangrove Kedatim tourism area in Sumenep has significant potential as an environmentally-based ecotourism destination. However, it faces various challenges and issues in carrying out effective and efficient promotional activities and digital communication management. To address these challenges faced by the tourism managers, a training program on digital communication content management based on the Blue Economy was conducted. The aim was to enhance both the quantity of promotional efforts and sustainable awareness among tourism managers from various environmental backgrounds. Method: A participatory approach through workshops, practical sessions on creating digital content such as photos, videos, and narratives, as well as strengthening the understanding of the Blue Economy concept. The training activity was attended by 30 participants from various community groups around the Mangrove Kedatim area. Results: Increase in participants’ understanding by approximately 42%, based on a comparison between pre-test and post-test scores. About 80% of participants were able to produce relevant promotional digital content, and 70% committed to applying digital communication strategies in managing tourism activities. Conclusion: This training was highly effective in improving digital skills and sustainable awareness, and it holds strong potential for promoting Mangrove Kedatim tourism in a more targeted way, with positive economic and environmental impacts.